PENINGKATAN HASIL BELAJAR IPA MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS VI DI SDN GUNUNG BUNDER 01 PAMIJAHAN - Muhammad Aldiansyah (INSTRUKTUR, 2023)
This study aims to find out how to improve the quality of learning activities so that they are more effective, so as to be able to improve science learning outcomes for class VI students. Research conducted using the Classroom Action Research approach Suharsimi Arikunto (2017: 19) defines Classroom Action Research as "Systemic Inquiry" conducted by teachers, principals, or school counselors to collect information about various schooling practices, including improving student learning outcomes.The results of this study indicate that in the initial conditions (pre-cycle) student learning outcomes are very low, this is evidenced by the number of students who achieve KKM only 8 students of 18 students, with the lowest score of 40 and the highest score of 80. In cycle I it was seen that student learning outcomes had increased, as many as 14 students achieved KKM with the lowest score of 60 and the highest score of 100. In cycle II, student learning outcomes increased with well this is based on formative test scores at the end of the lesson. 18 students (100%) experienced an increase in learning outcomes, although there was still 1 student (6%) who scored below the KKM. Using audio-visual media can improve student learning outcomes in science lessons on living things' adaptation to their environment